TEXTBOOK DEVELOPMENT ON ADDITIVE AND ADDICTIVE MATERIALS USING INQUIRY BASED LEARNING STEM APPROACH IN INCREASING STUDENT SCIENCE LITERACY - Isna, Isnanik; Rif’atul Himmah (Universitas Negeri Surabaya, 2024)
The purpose of this research was to develop textbook as teaching materials on additive and addictive materials using inquiry based learning model and STEM approach in increasing students’ scientific literacy. The method of this research was development research with ADDIE model. The qualitative data came from suggestions, while the quantitave data came from likert and guttman questionnaire and also the result of SPSS data processing. The result of this research, inquiry based learning with STEM approach made students to identify scientific issues, explain scientific phenomena, and use scientific evidence in everyday life. From validation result showed a very valid category, and pretest-posttest result showed an n-gain percentage of 80.17% (very effective). It can be conclude that the implementation of textbook with the inquiry based learning model and STEM approach was effectively used in learning to increase students’ scientific literacy.